A Study on Breast Cancer Awareness among Female Patients Attending a Tertiary Care Hospital - B. Kanchana, N. Sundharrajan2 , B. Krishnaprasanth3 , N. Aravindha Babu4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Breast cancer accounts for 19-34 % of all cancer cases among women in India. There is a high mortalityassociated with breast cancer due to late stage diagnosis, as patients usually present at an advanced stageof the disease. This can be attributed to factors like lack of awareness among the patients and non-existentbreast cancer screening programs. This study highlights the need for awareness about breast cancer amongwomen, propagation of valid information regarding the disease and promotes early detection of breast cancer